Osteoporosis Knowledge, Self-Efficacy, and Beliefs among College Students in the USA and China - M. Allison Ford; Martha Bass; Yan Zhao; Jin-Bing Bai; Yue Zhao (Journal of Osteoporosis)
This study investigated differences in osteoporosis knowledge, self-efficacy, and health beliefs among Chinese and American college students. Information obtained will be used in developing osteoporosis prevention programs for younger adults. Methods. Chinese (𝑛=409) and US (𝑛=408) college students completed the Osteoporosis Health Belief, Self-Efficacy, and Knowledge Tests. Results. Differences were seen in osteoporosis knowledge (𝑀us=14.52, 𝑀Chinese=11.82), exercise knowledge (𝑀us=8.16, 𝑀Chinese=9.04), calcium knowledge (𝑀us=8.47, 𝑀Chinese=9.73), perceptions of exercise benefits (𝑀us=24.07, 𝑀Chinese=21.09), calcium benefits (𝑀us=23.17, 𝑀Chinese=18.36), exercise barriers (𝑀us=11.75, 𝑀Chinese=14.96), calcium barriers (𝑀us=13.04, 𝑀Chinese=15), and exercise self-efficacy (𝑀us=73.71, 𝑀Chinese=63.81). Conclusion. US college students know more about osteoporosis and its risk factors; however, there are similarities in perception of risk between US and Chinese students. Chinese students perceive greater barriers to reducing their risk through exercise and dietary calcium intake.